Kinetics of endocan in patients undergoing cardiac surgery with and without cardiopulmonary bypass. (October 2018) - Poinsot, Pierre-Alain; Barrucand, Benoit; Ecarnot, Fiona; Lassalle, Philippe; Besch, Guillaume; Chocron, Sidney; Perrotti, Andréa
Highlights: Endocan plays a major role in inflammation and infection. We describe kinetics of endocan in cardiac surgery with and without CPB. Kinetics of endocan release differs according to whether surgery is on- or off-pump. In patients with CPB, endocan peaks and is significantly higher at 6 h after surgery. In off-pump surgery, endocan peaks at 24 h after surgery, then declines gradually. Abstract: Background: Endocan plays an important role in the processes of inflammation and infection. The use of cardiopulmonary bypass (CPB) during cardiac surgery can induce an inflammatory response. We aimed to describe the kinetics of endocan in patients undergoing cardiac surgery with and without the use of CPB. Methods: Single-centre, observational study with retrospective analysis of prospectively collected data, to compare the kinetics of endocan in patients undergoing isolated coronary artery bypass graft (CABG) surgery. Endocan was measured at induction of general anesthesia (baseline), and at 6, 24, 48 and 72 h after the end of surgery. Patients were classified into two groups, namely those undergoing CPB (CPB group) and those without CPB (off-pump group). Results: In total, 91 patients were included in this analysis: 61 patients in the CPB group and 30 in the off-pump group. There were no major significant differences between groups. Patients with CPB had a significantly higher level of endocan at 6 h (9.7 ± 6.7 ng/ml vs 6.9 ± 3.3 ng/ml, p = 0.03), but the difference was no longer statistically significant at subsequent timepoints. Endocan values were not significantly correlated with the duration of CPB (p = 0.53). Conclusion: Endocan levels in patients undergoing isolated CABG surgery with CPB are significantly higher at 6 h than in patients with off-pump surgery, and peaks earlier in those with CPB (6 h) than in those undergoing off-pump surgery (24 h).